Pengembangan Usaha Mikro Kecil Menengah Berbasis Agribisnis di Desa Paseh Kidul, Kecamatan Paseh, Kabupaten Sumedang - Pipin Supinah; Imran Yusuf; Eko Ruddy Cahyadi (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
The Community Service program is a form of concern from institutions, especially the Bogor Agriculture Institute, for the people of Indonesia. The concentration of IPB in general is in the development of the agricultural sector especially Agribusiness for Sumedang Regency. Therefore, in 2019 one of the community service programs was carried out in the Paseh Kidul Village, which was expected to show the contribution of students in empowering local resources in increasing the potential of agriculture, the economy, animal husbandry, and existing human resources. This activity aims to optimize the economic potential, human resources, and natural resources, especially in the development of agribusiness-based Micro Small and Medium Enterprises. The products that have been produced will later be able to develop into MSMEs, so that hopes for the future can create jobs and can improve people's welfare. Keywords: KKN-T, economic potential, MSME resources